Production of a dead oil well by a progressive cavity pump and its optimization - Tsapla Fotsa, Rolande; Ndemanou, Buris Peggy; Kemnang Tsafack, Alex Stephane; Fotie Foka , Noel Freddy; Sontia Fouazong, Darel (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
In the context of oil and gas extraction, a dead well refers to a well that has ceased to produce hydrocarbons. The major problems that account for this are: the reservoir has been depleted, the pressure has dropped too low to allow for extraction, or there are technical issues such as blockages or equipment failure. The main objective of this paper is to analyze the performance of a dead well called K88 (for confidential reasons) activated by the progressive cavity pump (PCP) in order to improve and maximize the oil flow rate produced. The completion, reservoir, production pressure, volume, and temperature (PVT) data are processed under Excel and Prosper software by using nodal analysis, sensitive analysis, economic analysis, and decline curve methods to obtain the results. The results showed that well K88 activated by the PCP has an oil flow rate of 1600.9 STB/day. The optimization makes it possible to obtain a net oil flow rate of 2005 STB/day associated with a head pressure of 45 psig. According to the economic calculation results, a gain in production is noticed during 10 years of production and a return on investment at the latest 39 days of production.